ETS transcription factor ETV2/ER71/Etsrp in hematopoietic and vascular development, injury, and regeneration. Issue 4 (2nd March 2017) - Zhao, Haiyong; Xu, Canxin; Lee, Tae‐Jin; Liu, Fang; Choi, Kyunghee
Abstract : The major goal in regenerative medicine is to repair and restore injured, diseased or aged tissue function, thereby promoting general health. As such, the field of regenerative medicine has great translational potential in undertaking many of the health concerns and needs that we currently face. In particular, hematopoietic and vascular systems supply oxygen and nutrients and thus play critical roles in tissue development and tissue regeneration. Additionally, tissue vasculature serves as a tissue stem cell niche and thus contributes to tissue homeostasis. Notably, hematopoietic and vascular systems are sensitive to injury and subject to regeneration. As such, successful hematopoietic and vascular regeneration is prerequisite for efficient tissue repair and organismal survival and health. Recent studies have established that the interplay among the ETS transcription factor ETV2, vascular endothelial growth factor, and its receptor VEGFR2/FLK1 is essential for hematopoietic and vascular development. Emerging studies also support the role of these three factors and possible interplay in hematopoietic and vascular regeneration. Comprehensive understanding of the molecular mechanisms involved in the regulation and function of these three factors may lead to more effective approaches in promoting tissue repair and regeneration. Developmental Dynamics 246:318–327, 2017 . © 2016 Wiley Periodicals, Inc. Key Findings: Etv2 is critical for hematopoietic and vascular development. While Etv2 expression becomes silent in hematopoietic and endothelial cells once hematopoietic and vascular systems have become established, its expression is reactivated in hematopoietic stem cells or endothelial cells upon injury. Etv2 reactivation is necessary for successful hematopoietic or vascular regeneration upon injury.